Limites e condicionantes à expansão da soja em Mato Grosso e no complexo MAPITOBA: uma abordagem utilizando econometria espacial - PESSOA, Ruben Eurico da Cunha (Universidade Federal do Pará, 2017)
This thesis aims to analyze the determining factors of soybean expansion in Mato Grosso and MAPITOBA complex. It was found that a relationship exists spatial dependence inside producers mesoregion. The spatial dependence is represented by the attempt agglomeration of polygons (soy municipalities producers) around one or more attributes that makes that particular region. This is possible in the case of soybeans, when conditioning factors necessary for production are present, namely: a) Soil and relief; b) Requirements climate like water, light and temperature; c) Infrastructure and logistics for delivery of inputs and pesticides, as well as the run off of production; and d) Financing of production. In the presence of these conditioning factors is possible the expansion of soybean production. Soybean producers states such as Mato Grosso and those belonging to the conglomerate MAPITOBA hold about 48,8 million hectares of savanna coverage in his clenched, which corresponds to 64.55% of the quoted physiognomy of the entire biome. Thus, there remain 26,8 million hectares (35,45%) of this type of coverage that can sustain the growth of the planted area in the coming years. Corroborating the possibility of expansion were estimated coefficients of elasticity of the largest soybean producing that unity through spatial econometric models. The water availability in the Cerrado is dependent on the large amount of water vapor formed in the Amazon Biome. The intensive use of irrigation by means of pivots in crops, expansion of biodiesel production from oil certainly will raise the demand for water resources in any production region and can compromise the water supply to users and their multiple uses in agriculture if there is no efficient resource management in river basins of the Cerrado. In the medium term, agribusiness depends on water availability in the Cerrado and the Amazon ecosystem services for the cultivation of soy and its expansion in the producers regions.